Registration of the ocurrence of Aedes albopictus in an urban zone in Manaus, Amazonas, Brazil - Fé, Nelson Ferreira; Barbosa, Maria das Graças Vale; Alecrim, Wilson Duarte; Guerra, Marcus Vinitius de Farias (Revista de Saúde Pública, 2003)
Information is available regarding the presence of Aedes albopictus in several municipalities of the State of Amazonas. Specimens of this mosquito species have now, for the first time, been collected from an urban area of the municipality of Manaus, Amazonas, Brazil.